Neoadjuvant chemoradiotherapy for resectable gastric cancer: A meta-analysis - Chen, Jiuzhou; Guo, Yaru; Fang, Miao; Yuan, Yan; Zhu, Youqi; Xin, Yong; Zhang, Longzhen (Frontiers in Oncology, 2022)
Objectives To evaluate the clinical curative effects and toxicity of neoadjuvant chemoradiotherapy for resectable gastric cancer compared to those of neoadjuvant chemotherapy. Methods A systematic review and meta-analysis of the randomized controlled trials (RCTs) of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy were performed in patients with resectable gastric cancer. Results Seven RCTs were included (601 patients; 302 in the neoadjuvant chemoradiotherapy group and 299 in the neoadjuvant chemotherapy group). The neoadjuvant chemoradiotherapy group had an increased number of patients with a complete response [odds ratio (OR) = 3.79, 95% confidence interval (CI): 1.68–8.54, p = 0.001] and improved objective response rate (OR = 2.78, 95% CI: 1.69–4.57, p < 0.0001), 1-year (OR = 3.51, 95% CI: 1.40–8.81, p = 0.007) and 3-year (OR = 2.14, 95% CI: 1.30–3.50, p = 0.003) survival rates, R0 resection rate (OR = 2.21, 95% CI: 1.39–3.50, p = 0.0008), and complete pathologic response (OR = 4.39, 95% CI: 1.59–12.14, p = 0.004). Regarding the incidence of adverse effects after neoadjuvant therapy, only the occurrence rate of gastrointestinal reaction in the neoadjuvant chemoradiotherapy group was higher than that in the neoadjuvant chemotherapy group (OR = 1.76, 95% CI: 1.09–2.85, p = 0.02), and there was no significant difference in other adverse effects. There was no difference in the incidence of postoperative complications between the two groups. Conclusion Neoadjuvant chemoradiotherapy for resectable gastric cancer has several advantages in terms of efficacy and safety compared to neoadjuvant chemotherapy. Therefore, neoadjuvant chemoradiotherapy has great potential as an effective therapy for resectable gastric cancers. Systematic Review Registration https://inplasy.com/inplasy-2022-3-0164, registration number INPLASY202230164.